Effect of posture on lung ventilation distribution and associations with structure in children with cystic fibrosis - Ramsey, K.; McGirr, C.; Stick, S.; Hall, Graham; Simpson, S. (Elsevier, 2016)
Background: We assessed the effect of posture on ventilation distribution and the impact on associations with structural lung disease. Methods: Multiple breath washout (MBW) was performed in seated and supine postures in 25 healthy children and 21 children with CF. Children with CF also underwent a chest CT scan. Functional residual capacity (FRC), lung clearance index (LCI) and moment ratios were calculated from the MBW test. CT scans were evaluated for CF-related structural lung disease. Results: FRC was lower in the supine than in the seated posture, whereas LCI was higher in the supine than in the seated posture. In children with CF, associations between LCI and the extent of structural lung disease were stronger when performed in the supine posture. Conclusions: Body posture influences lung volumes and ventilation distribution in both healthy children and children with CF. MBW testing in the supine posture strengthened associations with structural lung damage.